Tackling ethnic inequality in forensic mental healthcare - Smith, Shubulade (Seminars in forensic psychiatry, 2024)
There are well-known, significant racial disparities in mental healthcare access, experience and outcome. The additional duty of forensic mental health practitioners to be always mindful of public protection means that it is imperative that all steps are taken to reduce the risk that individuals with mental disorder may pose to others, as well as themselves. Forensic mental healthcare focusses on secondary prevention - preventing known patients from relapsing and re-offending – recurrence of violence. The evidence increasingly points to the fact that forensic mental health services are doing this more successfully with some sections of the population we serve than others.